A technique of staged lateral release to correct patellar tracking in total knee arthroplasty - Strachan, R.K.; Merican, A.M.; Devadasan, B.; Maheshwari, R.; Amis, A.A. (Elsevier, 2009)
Optimal patellar tracking and component alignment are important in achieving a well-functioning total knee arthroplasty (TKA). The patella is constrained partly by design of the prosthetic trochlear groove, and patellar tracking is governed by a combination of static and dynamic factors. Maltracking may result from excessive or unbalanced tension in the surrounding soft tissues. This article describes a staged progressive lateral release of the patellar retinaculum in TKA, which is classified into 6 stages. Stage 1 transects the deep lateral patellofemoral ligament; stages 2 to 6 extend the lateral patellar incision distally from vastus lateralis to the tibial tubercle. This technique was used in a series of 96 primary TKAs. We report the rates of the various stages of lateral release and the variables that might affect the decision to perform such a release.